2016
DOI: 10.1074/jbc.m115.706523
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanolamine Is a Key Regulator of Membrane Fluidity in Eukaryotic Cells

Abstract: Adequate membrane fluidity is required for a variety of key cellular processes and in particular for proper function of membrane proteins. In most eukaryotic cells, membrane fluidity is known to be regulated by fatty acid desaturation and cholesterol, although some cells, such as insect cells, are almost devoid of sterol synthesis. We show here that insect and mammalian cells present similar microviscosity at their respective physiological temperature. To investigate how both sterols and phospholipids control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
210
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(230 citation statements)
references
References 31 publications
19
210
1
Order By: Relevance
“…Cells must maintain their membrane integrity and structure to function properly, and one way that they combat changes to membrane fluidity is to alter the membrane composition by adjusting the ratio of certain lipids, particularly cholesterol (to decrease fluidity) and phosphatidylethanolamine (PE, to increase fluidity) (Dawaliby et al , 2016). We have previously shown that, like other bacterial toxins, e.g., (Alonso et al , 2000; Boesze-Battaglia et al , 2009; Farrand et al , 2010; Lai et al , 2013; Maxfield and Tabas, 2005; Patel et al , 2002; Schwiering et al , 2013; Zitzer et al , 2001), LtxA requires cholesterol in the plasma membrane to bind and kill target cells (Brown et al , 2013; Brown et al , 2015; Fong et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cells must maintain their membrane integrity and structure to function properly, and one way that they combat changes to membrane fluidity is to alter the membrane composition by adjusting the ratio of certain lipids, particularly cholesterol (to decrease fluidity) and phosphatidylethanolamine (PE, to increase fluidity) (Dawaliby et al , 2016). We have previously shown that, like other bacterial toxins, e.g., (Alonso et al , 2000; Boesze-Battaglia et al , 2009; Farrand et al , 2010; Lai et al , 2013; Maxfield and Tabas, 2005; Patel et al , 2002; Schwiering et al , 2013; Zitzer et al , 2001), LtxA requires cholesterol in the plasma membrane to bind and kill target cells (Brown et al , 2013; Brown et al , 2015; Fong et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The radius of spontaneous curvature of cholesterol is tightly negative (R 0 ¼ 220 Å ) [56] and hence in a bilayer arrangement, frustration of the spontaneous curvature of cholesterol is one mechanism through which membrane order might be controlled. This suggests that other lipids with negative spontaneous curvature will also increase membrane order when their curvature is frustrated, as a recent in vivo study that replaces cholesterol with PE indicates [59].…”
Section: A Mechanism For Phospholipid Homeostasis: Curvature Elastic mentioning
confidence: 98%
“…PE depletion results in decreased transmembrane potential across the inner mitochondrial membrane, and this results in impaired mitochondrial function [54]. In addition, PE has been shown to be important in regulating membrane fluidity [55]. Fusion of phospholipid vesicles with organelles like mitochondria results in organelle swelling and dilution of membrane components that are normally compacted into dense super complex structures for maximal interactions [56].…”
Section: Membrane Lipid Replacement-in Vitro Studiesmentioning
confidence: 99%